Розвиток у різних країнах світу системи безперервної освіти - Orosz Ildikó; Орос Ільдіко; Oros Ildiko; Черничко Степан; Csernicskó István; Csernicsko Istvan (Видавництво «Код», 2025)
Резюме. Значну роль у становленні й розвитку освіти дорослих у Європі і взагалі у світі відіграють наукові конференції та інші міжнародні зв’язки. У статті показано роль міжнародних зв’язків у розвитку системи освіти дорослого населення. Визначено перешкоди на цьому шляху. Проблемі освіти дорослих приділяється суттєва увага в освітній політиці розвинутих країн ЄС. Вона розглядається як механізм досягнення стійкого економічного розвитку, гарантування громадянського прогресу та демократичного устрою суспільного життя; як вияв відповідальності суспільства за формування людського та соціального капіталу, який є ключовим елементом сучасного суспільства знань.

Abstract. A significant role in the formation and development of adult education in Europe and in the world in general is played by scientific conferences and other international relations. The article shows the role of international relations in the development of the adult education system. Obstacles on this path are identified. The problem of adult education is given significant attention in the educational policy of developed EU countries. It is considered as a mechanism for achieving sustainable economic development, guaranteeing civic progress and a democratic structure of public life; as an expression of society’s responsibility for the formation of human and social capital, which is a key element of the modern knowledge society. The experience of the formation and development of the system of continuing adult education in different countries of the world is briefly described Іn recent years, in the context of modern tasks for the development of continuing education in advanced countries of the world, a positive trend has been observed: the professional culture of specialists is analyzed at an interdisciplinary level, in the context of the categories of philosophy, history of continuing vocational education, culturology, andragogy, didactics of vocational schools, methods of teaching vocational disciplines and industrial training, and vocational training of the unemployed. As can be seen from the study, in countries with a more educated population, social inequality in formal adult education is lower, which may be because in countries with a more educated population, less educated workers have a higher motivation to increase their level of education.
Development of continuous education systems in different countries of the world
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00015727 Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-13
Keywords: країни світу; система безперервної освіти; освіта дорослих; формування особистості; професійна культура майбутніх фахівців